Test rig for micro gear and experimental analysis on the meshing condition and failure characteristics of steel micro involute gear and metallic glass one - Niza, M.E.; Komori, M.; Nomura, T.; Yamaji, I.; Nishiyama, N.; Ishida, M.; Shimizu, Y. (Elsevier, 2010)
A test rig to evaluate the performance of a micro involute gear with a diameter below 1 mm has been developed. Shaft position and shaft center distance of gears have great influence on the gear performance and therefore they must be adjusted precisely. In this research, the measurement and adjustment method of gear assembly condition and an in-situ observation system of gear condition are proposed, that are appropriately designed for micro gears. The meshing condition of micro involute gears is investigated experimentally. Based on the observation of sliding marks on the tooth flank, it is clarified that the meshing condition of a micro involute gear follows the meshing theory of an involute gear. Failure modes of SK4 micro gears and metallic glass micro gears are investigated. The experimental results indicated that SK4 micro gears suffer severe wear under unlubricated conditions that generate powderlike wear particles. On the other hand, flakelike wear particles appear in the metallic glass micro gear. (C) 2010 Elsevier Ltd. All rights reserved.